Metabolism of apolipoproteins AI and AII in subjects carrying similar apoAI mutations, apoAI Milano and apoAI Paris - Perez-Mendez, Oscar; Bruckert, Eric; Franceschini, Guido; Duhal, Nathalie; Lacroix, Brigitte; Bonte, Jean-Paul; Sirtori, Cesare; Fruchart, Jean-Charles; Turpin, Gérard; Luc, Gérald (Atherosclerosis, 2000)
ApoAI Milano (AI M) and apoAI Paris (AI P) are mutant forms of apoAI in which cysteine is substituted for arginine at residues 173 and 151 respectively leading to the formation of homodimers and heterodimers with apoAII. Heterozygous subjects with these mutants are characterized by low levels of plasma HDL cholesterol and apoAI. The present study analyzed the metabolism of the different complexes of apoAI in three subjects, two AI M and one AI P, using a primed-constant infusion of trideuterated leucine. In AI M carriers, the mutant form was almost equally distributed in AI M dimer, AI M:AII heterodimer and the monomer, whereas, in the AI P subject, the mutant apoAI was essentially in the apoAI P:AII complex. Normal apoAI was low in the AI M subjects (20 and 16 mg/dl) but very low in the AI P subject (0.3 mg/dl). In the AI M subjects, the low levels of apoAI were due to a rapid catabolism with a normal synthetic rate. However, the apoAI kinetics were heterogeneous with a rapid catabolism of the AI M:AII complex (FCR of 0.430 and 0.401 day −1) and the AI M monomer (FCR of 0.570 and 0.406 day −1) whereas the AI M dimer was catabolized slowly (FCR of 0.114 and 0.118 day −1). In contrast, AI P was catabolized relatively slowly with a FCR of 0.263, 0.182 and 0.258 day −1 for AI P homodimer, apoAI P:AII heterodimer and AI P monomer. In the three subjects, normal apoAI was catabolized quickly, with an FCR of 0.805 and 0.601 day −1 in AI M carriers and 0.526 day −1 in the AI P carrier. Therefore, the low level of apoAI in the AI P carrier is caused by a low production rate of apoAI, particularly of normal apoAI. In conclusion, apoAI is kinetically heterogeneous in AI M and in AI P subjects. Moreover, the two mutations lead to significant differences in the kinetic behavior of mutant apoAI depending on its inclusion in its complexes.